2023
DOI: 10.3390/diagnostics13030469
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Capsule Endoscopy within 6 Hours Following Bowel Preparation with Polyethylene Glycol Shows Improved Small Bowel Visibility

Abstract: Although bowel preparation influences small bowel visibility for small bowel capsule endoscopy (SBCE), the optimal timing for bowel preparation has not been established yet. Thus, the aim of the study was to evaluate the optimal timing of polyethylene glycol (PEG) for small bowel preparation before SBCE. This multicenter prospective observational study was conducted on patients who underwent SBCE following bowel preparation with polyethylene glycol (PEG). Patients were categorized into three groups according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Therefore, we consider that the shorter time required for the preparation in Group C (2 h) than that required in Group B (at least 4 h) might have worked as effectively for the visibility of the distal ileum rather than the direct effect of colonoscopy. Although the optimal timing for bowel preparation has not yet been established, Choi CW et al recommended that faster bowel preparation should be performed (within 6 h before SBCE) for improved distal small bowel examination [6]. Our results are considered to be consistent with this report.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, we consider that the shorter time required for the preparation in Group C (2 h) than that required in Group B (at least 4 h) might have worked as effectively for the visibility of the distal ileum rather than the direct effect of colonoscopy. Although the optimal timing for bowel preparation has not yet been established, Choi CW et al recommended that faster bowel preparation should be performed (within 6 h before SBCE) for improved distal small bowel examination [6]. Our results are considered to be consistent with this report.…”
Section: Discussionsupporting
confidence: 89%
“…Second, this study did not examine the finding rates. A recent paper reported that there was no significant difference in finding rates between different timing of laxative intake, but there was a significant difference in visibility, especially in the distal small bowel [6]. Even if there was no significant difference in finding rates in our study, we believe it was useful.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Blurred intestinal fluid, air bubbles, and food particles may impair the visibility of the small intestine and decrease the diagnostic yield. 2 Nevertheless, the optimal bowel cleaning regimen has not been defined yet in the literature. Generally, overnight fasting (at least 12 hours) and clear fluid ingestion only are recommended.…”
Section: Introductionmentioning
confidence: 99%